2018
DOI: 10.1002/anie.201809050
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Mediated Synthesis of Cyclobutane Isomers in a Photoactive Cadmium(II) Porous Coordination Polymer

Abstract: Photochemical [2+ +2] cycloaddition of 1,4-bis[2-(4pyridyl)ethenyl]benzene,c arried out in aC d II porous coordination polymer (PCP), produces different isomeric products depending on the guest solvent present in the PCP during irradiation. The nature of the included guest influences the conformation of the ligand, and thus the outcome of the cycloaddition reaction. We demonstrate controlled production of the two isomers from the same PCP by simple exchange of solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 42 publications
(107 reference statements)
0
29
0
Order By: Relevance
“…Over the past decades, [2 + 2] photocycloaddition reactions have been widely applied to the synthesis of specific cyclobutanes because they represent high yielding single transformations. However, cyclobutanes have four stereocenters, and their control suffers from relatively poor regio- and stereoselectivity 3 9 . Various supramolecular templates 10 12 , host-guest assemblies 13 , 14 , quantum dots 15 , chiral molecular catalysts 16 18 , and Lewis acid cocatalysts 19 , 20 have been developed to control the enantioselectivity and diastereoselectivity of [2 + 2] photocycloaddition transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, [2 + 2] photocycloaddition reactions have been widely applied to the synthesis of specific cyclobutanes because they represent high yielding single transformations. However, cyclobutanes have four stereocenters, and their control suffers from relatively poor regio- and stereoselectivity 3 9 . Various supramolecular templates 10 12 , host-guest assemblies 13 , 14 , quantum dots 15 , chiral molecular catalysts 16 18 , and Lewis acid cocatalysts 19 , 20 have been developed to control the enantioselectivity and diastereoselectivity of [2 + 2] photocycloaddition transformations.…”
Section: Introductionmentioning
confidence: 99%
“…However,owing to the limited types of diolefins, there are only af ew examples of diolefinsw hich can undergo solid-state[ 2 + +2] photo-polymerization/dimerization in their crystalline state. [15][16][17] The dipyridyl compound 1,4-bis(pyridin-4-yl)-1,3-butadiene (bpbde) is ac onjugated diolefin. Each pair of the nearest molecules of 1,4bpbde mayb ea ligned to be photoreactivei ne ither in-phase or out-of-phase fashion( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[10] Furthermore, due to their tunable struc-tures, the arrangementmodes of olefinic molecules in the crystalline CPs may also be regulated by minor changes of reaction conditions. [17] In order to augment the photoreactivity of ad iolefin and prepared ifferent photoproducts, the utilization and adjustment of auxiliary ligands may be an efficient method. To our knowledge,t he syntheses of different photodimer isomers based on regio-or stereo-selective photoreactions of bpbde by tuning of similar auxiliary ligands has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of universality is the main obstacle for the practical utilization of topochemical reactions in organic synthesis. In this regard, flexible metal–organic frameworks (MOFs) , can be envisaged as good platform materials for performing diverse topochemical reactions including selective, multipoint, or reversible olefin/olefin cyclization. MOFs have not only a wide variety of pore structures suitable to confine reactants but also exhibit flexibility in the sense that structures can be transformed by external stimuli such as inclusion and exclusion of guest molecules. In addition, MOF structures can be chemically modified by photoirradiation. Recently, it has been shown that different products can be obtained by adding different guest molecules to the MOF, thereby altering the pair of reactive molecules . Since the molecular arrangement in flexible MOFs can be finely tuned, it would be expected that reaction positions and reactivity of substrates would be also controllable.…”
mentioning
confidence: 99%
“…34−36 Recently, it has been shown that different products can be obtained by adding different guest molecules to the MOF, thereby altering the pair of reactive molecules. 37 Since the molecular arrangement in flexible MOFs can be finely tuned, it would be expected that reaction positions and reactivity of substrates would be also controllable.…”
mentioning
confidence: 99%